Tourist Destination Governance: Practice, Theory and Issues - Laws, Eric (CABI, 2014)
The aims of this book are to contribute to the understanding of best practices in tourist destination governance and to benchmark and advance ways of theoriz- ing on these practices. Tourism is recognized as a complicated, multi-sector activ- ity with numerous stakeholders and with diverse and often divergent goals and objectives. Achieving cooperation, collaboration and integration among the gov- ernment organizations involved in the various aspects of tourism and between government and private sector enterprises, as well as between tourism policies and community interests, are major concerns for policy makers, managers, com- munity members and academics. Further difﬁ culty is due to the need for a tourist destination to deal with changing tastes, interests and concerns among its visi- tors, and ﬂ uctuations in market conditions due to crises and disasters. It is also widely accepted that tourism has varied and rapidly evolving forms, meaning that each destination system must be understood in its own contexts. All human (social and economic) systems depend on the performance of generic functions. ‘Any system has to cope with external challenges, to prevent conﬂ icts amongst its members … to procure resources … and to frame goals and policies to achieve them’ (Rosenau and Czempiel, 1992:3). We may consider that governance is the means by which a system seeks to ensure these functions are undertaken. Governance is the set of tasks such as decision making, enforce- ment of decisions, communication of rules and measurement of performance that allow these functions of a system to proceed.